Methodological principles of implementing biosphere-compatible housing construction - Nazvanov, Denys (Ways to Improve Construction Efficiency, 2024)
The article discusses the methodological foundations of implementing biosphere-compatible housing construction as an important stage in the development of sustainable housing construction, which takes into account the ecological, economic, and social aspects of environmental preservation. Given that increasing urbanization and climate change threaten the health of ecosystems and people, the adaptation of construction concepts to the principles of biosphere compatibility is crucial. These principles not only aim to preserve natural resources but also to restore ecological balance, ensuring that future generations can live in a healthy and sustainable environment. The goal of biosphere-compatible construction is to develop and implement methods that minimize the negative impact on the environment, ensure the efficient use of natural resources, and create conditions for comfortable living. By employing innovative building materials and advanced technologies, it is possible to reduce energy consumption, improve resource management, and enhance the resilience of buildings to environmental changes. The article proposes a system of methods and approaches that allow for balancing the housing needs of humanity with the preservation of ecosystems. Special attention is given to the analysis of modern construction technologies focused on energy efficiency, the use of renewable materials, and eco-friendly energy sources, such as solar and wind energy, which can significantly reduce the carbon footprint of housing developments. The article also describes the main principles of biosphere-compatible design, including the integration of natural elements into architectural solutions, the use of resource-saving technologies, and the adaptation of buildings to climate change. This approach ensures that buildings are not only energy-efficient but also capable of withstanding extreme weather conditions, such as floods and heatwaves, which are becoming more frequent due to climate change. The aspects of residential complex infrastructure development are discussed separately, focusing on ensuring the sustainability of the urban environment through the development of eco-friendly transportation systems, green spaces, as well as infrastructure for waste recycling and water conservation. Such features not only help reduce the environmental impact but also improve the quality of life for urban residents.